The Effectiveness of an Islamic Approach based on the Balance Selection in Improving Quality of Life, Happiness, and Life Satisfaction of Married Women - Kordloo, Monireh; Sanaei Zaker, Bagher; Khalatbari, Javad (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the effectiveness of an Islamic approach based on balance selection on the quality of life, happiness, and life satisfaction of women. Methods: The study was quasi-experimental with a pretest-posttest design, experimental and control groups, and quarterly follow-up. The statistical population consisted of married women who visited counseling centers of the Psychology and Counseling Organization in 2018. In the study, 28 married women were selected by a purposive method and were randomly assigned to two 14-individual groups, experimental and control. The research tools included Life Satisfaction Questionnaire by Diner et al. (1985), Short-Form Health Survey by Ware & Sherbourne (1992), and Oxford Happiness Inventory by Argyle et al. (1989). The experimental group was trained with the researcher-made Islamic approach based on the balance selection in twelve sessions, and the control group did not receive any training. Data were analyzed using repeated-measures analysis of variance. Results: The results indicated that the Islamic approach based on balance selection was effective in improving quality of life (P=0.014, F= 6.20), life satisfaction (P=0.002, F=7.72), and happiness (P=0.047, F=3.15) in married women, and the effect was stable in the follow-up phase. Conclusion: The results showed that the Islamic approach psychotherapy based on balance selection had a stable effect of treatment on the quality of life, happiness, and satisfaction of women who visited counseling centers of the Psychology and Counseling Organization in Tehran. Therefore, this method can be used as an effective intervention method to increase the quality of life, happiness, and satisfaction of people, especially married women.